A model for optimizing cycling performance by varying power on hills and in wind - Swain, D. P. (Medicine & Science in Sports & Exercise, 1997)
When compared to even energy expenditure (constant effort) strategies for endurance events, it was found that significant time savings could be realized on hilly and windy courses by slightly increasing power on uphill or headwind segments while compensating with reduced power on downhill or tailwind segments. Implication: Constant effort performances will not yield the best performances under variable terrain and atmospheric conditions. It is best to work a little harder under difficult circumstances (e.g., headwind, hills) and to work a little easier under favorable conditions (e.g., downhill, tailwinds).